Exotic invasive plants increase productivity, abundance of ammonia‐oxidizing bacteria and nitrogen availability in intermountain grasslands. (12th May 2016) - McLeod, Morgan Luce; Cleveland, Cory C.; Lekberg, Ylva; Maron, John L.; Philippot, Laurent; Bru, David; Callaway, Ragan M.
Summary: Exotic plant invasion is often associated with dramatic increases in above‐ground net primary productivity and soil nitrogen. However, most evidence for these increases comes from correlative studies of single species, leaving open the question of whether invasive plants drive these processes and whether they are consistent among invaders. We combined field surveys and measurements within experimental plantings to examine how plant productivity, soil nitrogen and the abundance of ammonia‐oxidizing bacteria (AOB) change in response to invasions by four exotic species. The relationship between plant productivity and soil nitrate differed among native and invasive species, suggesting a fundamental disparity in the effects of natives and invaders on ecosystem processes. In field surveys, dense patches of all invasive species had higher abundances of AOB than native‐dominated sites. Three of the four invasive species had higher productivity, soil nitrate concentrations and rates of potential nitrification as compared to nearby native‐dominated communities. In our experimental plantings, we found that two invasive species drove increases in soil nitrate and one invader caused increased productivity after a single season. Synthesis . Our results highlight the importance of the N cycling soil microbial community in how exotic invasive plants alter ecosystem function and show that shifts in function can occur rapidly. Abstract : Our results highlight the importance of the N cycling soil microbial community in how exotic invasive plants alter ecosystem function and show that shifts in function can occur rapidly.